Quantitative and semi-quantitative assessment of synovitis on MRI and the relationship with symptoms in symptomatic knee osteoarthritis - Perry, Thomas A; Yang, Xiaotian; van Santen, James; Arden, Nigel K; Kluzek, Stefan (Rheumatology (Oxford, England), 2021)
Abstract Objectives Synovitis in symptomatic knee OA (KOA) is common and is associated with joint symptoms. Optimal synovial measurement on MRI is, however, unclear. Our aims were to examine the relationship between MRI measures of synovitis and knee symptoms in symptomatic KOA. Methods Data from a randomized, multicentre, placebo-controlled trial (UK-VIDEO) of vitamin-D therapy in symptomatic KOA were utilized. Participants reported knee symptoms using WOMAC at baseline and annually. On contrast-enhanced (CE) MRI, synovial thickness was measured using established, semi-quantitative methods whilst synovial tissue volume (STV) was assessed as absolute STV (aSTV) and relative to the width of femoral condyle (rSTV). STV of the infrapatellar region was also assessed. Associations between synovial measures and symptoms were analysed using multiple linear regression modelling. Results No linear association was observed between knee symptoms and synovitis thickness scores. Whole-joint aSTV (0.88, 95% CI: 0.17, 1.59) and infrapatellar aSTV (5.96, 95% CI: 1.22, 10.7) were positively associated with knee pain. Whole-joint rSTV had a stronger association with pain (7.96, 95% CI: 2.60, 13.33) and total scores (5.63, 95% CI: 0.32, 10.94). Even stronger associations were found for infrapatellar rSTV with pain (55.47, 95% CI: 19.99, 90.96), function (38.59, 95% CI: 2.1, 75.07) and total scores (41.64, 95% CI: 6.56, 76.72). Conclusions Whole-joint and site-specific infrapatellar STV measures on CE-MRI were associated with knee pain, respectively. Volumes relative to the size of the femoral condyle may be promising outcome measures in KOA trials.